2018
DOI: 10.1002/cjp2.109
|View full text |Cite
|
Sign up to set email alerts
|

Association of p16 expression with prognosis varies across ovarian carcinoma histotypes: an Ovarian Tumor Tissue Analysis consortium study

Abstract: We aimed to validate the prognostic association of p16 expression in ovarian high‐grade serous carcinomas (HGSC) and to explore it in other ovarian carcinoma histotypes. p16 protein expression was assessed by clinical‐grade immunohistochemistry in 6525 ovarian carcinomas including 4334 HGSC using tissue microarrays from 24 studies participating in the Ovarian Tumor Tissue Analysis consortium. p16 expression patterns were interpreted as abnormal (either overexpression referred to as block expression or absence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 62 publications
8
49
0
Order By: Relevance
“…Among these studies, oestrogen receptor (ER)‐positive and progesterone receptor (PR)‐positive expression was shown to demonstrate survival advantage, but the subset of stage IC/II patients with expression of any of these two markers failed to reach the 5‐year survival threshold of 95% required for withholding adjuvant chemotherapy . Conversely, p16 identifies a subset of EC with unfavourable outcome …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, oestrogen receptor (ER)‐positive and progesterone receptor (PR)‐positive expression was shown to demonstrate survival advantage, but the subset of stage IC/II patients with expression of any of these two markers failed to reach the 5‐year survival threshold of 95% required for withholding adjuvant chemotherapy . Conversely, p16 identifies a subset of EC with unfavourable outcome …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Conversely, p16 identifies a subset of EC with unfavourable outcome. 8 The most common molecular alteration in EC occurs in CTNNB1. 9,10 CTNNB1 encodes b-catenin, a membrane-associated protein involved in the regulation of cellular adhesion and a key mediator in the Wnt signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…LGSOC cell lines were characterized by a strong enrichment of C>T and C>A nucleotide substitution mutations, a predominance of KRAS mutations, and CNA's that are characteristic of those described in previous reports of LGSOC [10,11]. Both LGSOC cell lines and tumors were characterized by a lower tumor mutation burden than other ovarian cancer subtypes.…”
Section: Discussionmentioning
confidence: 54%
“…However, in the last 5-10 years investigators have elucidated many key genomic aberrations, leading to major advancements in the molecular characterization and classification of LGSOC [3,4]. In contrast to other ovarian cancer subtypes, LGSOC are genetically characterized by high frequency of oncogenic mutations in KRAS, NRAS, and BRAF (20-40%, 7-26%, 5-33%, respectively) [5-7], a very low prevalence of TP53 mutations (<8%) [8,9], frequent copy-number deletion of CDKN2A resulting in loss of tumor suppressor protein p16 (15-53%) [10,11], and high expression of estrogen receptor (ER) and progesterone receptor (PR) (>90% and >50%, respectively) [12][13][14]. More recently, less frequent mutations in USP9X (15%) and EIF1AX (8%) have been described in a small proportion of LGSOC tumors [10,15].Traditionally, the therapeutic management of different ovarian cancer histotypes has been similar as it is now appreciated that different ovarian histological subtypes represent different diseases [16].Consequently, the most common treatment for LGSOC is based on cytoreductive surgery followed by platinum/paclitaxel chemotherapy.…”
mentioning
confidence: 99%
“…The prognostic role of p16 was examined in a large cohort of ovarian carcinoma patients (n = 6,525), wherein differences in prognosis were demonstrated across the five main histotypes of varying FIGO stages. Block expression (overexpression >90% of tumor cells are stained) of p16 was associated with shorter overall survival (OS) in CCC and EC, absence of p16 in LGSC correlated with shorter OS, while no prognostic significance was found for HGSC-or MC-patients (2). A further study showed an association between favorable outcome and ARID1A-and p53-expression, as well as negative nuclear/positive membrane expression for β-Catenin, in 97 ovarian [CCC (n = 11), EC (n = 21)] and endometrial [clearcell (n = 6) and endometrioid uterine (n = 59)] carcinomas.…”
Section: Introductionmentioning
confidence: 99%